Enantioselective Addition of Alkynyl Ketones to Nitroolefins Assisted by Brønsted Base/H‐Bonding Catalysis. Issue 17 (27th February 2019) - Campano, Teresa E.; Iriarte, Igor; Olaizola, Olatz; Etxabe, Julen; Mielgo, Antonia; Ganboa, Iñaki; Odriozola, José M.; García, Jesús M.; Oiarbide, Mikel; Palomo, Claudio
Abstract: Various sets of enolizable alkynyl ketones (including methyl ynones with α‐aryl, α‐alkenyl, and α‐alkoxy groups) were able to react smoothly with nitroolefins with the assistance of bifunctional Brønsted base/H‐bond catalysts to provide adducts with two consecutive tertiary stereocenters in a highly diastereo‐ and enantioselective fashion. Further transformation of the obtained adducts into optically active acyclic and polycyclic molecules, including some with intricate carbon skeletons, was also demonstrated. Abstract : Donor ynones : under very mild conditions linear ynones with no additional electron‐withdrawing group at Cα get activated by tertiary amine/squaramide chiral catalysts and react with nitroolefins in a highly diastereo‐ and enantioselective fashion. In this way, an easy access to branched alkyl alkynyl ketones with two contiguous stereocenters and derivatives thereof is provided.